Effect of computer assisted instruction web site for swimming to childrens' learning motives and learning strategy - Sengoku, Y.; Nomura, T. (Biomechanics and Medicine in Swimming X, 2006)
The present study was intended to identify the effect of a CA! web site for swimming to elementary school children's learning motives and learning strategy. Fifth-grade children participated in this study. Subjects were classified into two groups that learned with the CA! web site throughout the swimming class and a control group that merely participated in the ordinary swimming class inside the pool. Learning motives, a learning strategy and 25 m swimming performance were investigated before and after the swimming class. The superiority orientedmotive and aim learning strategy decreased significantly (p<0.05) after the swimming class in the control group. Using the CA! web site, it was indicated that the motivation to achieve higher swimming performance was kept high through the swimming class and that students were able to achieve a clear objective for their swimming class.